2016
DOI: 10.1016/j.ajog.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis: epidemiology and mode of delivery, 2005–2013

Abstract: BACKGROUND Gastroschisis is a severe congenital anomaly the etiology of which is unknown. Research evidence supports attempted vaginal delivery for pregnancies complicated by gastroschisis in the absence of obstetric indications for cesarean delivery. OBJECTIVE The objectives of the study evaluating pregnancies complicated by gastroschisis were to: (i) determine the proportion of women undergoing planned cesarean versus attempted vaginal delivery; and (ii) provide up-to-date epidemiology on risk factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
4
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 31 publications
5
52
4
12
Order By: Relevance
“…We found socioeconomic status (level of education and grade of profession) to be significantly higher in CG mothers compared to AWD mothers ( P = 0.05). Using multiple regression analysis, we confirmed this influence, and these results were supported by Shariff et al Among AWD mothers, the OC are employed significantly more often in higher rank or leading positions ( P = 0.039), and the data of Friedman et al confirmed these observations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found socioeconomic status (level of education and grade of profession) to be significantly higher in CG mothers compared to AWD mothers ( P = 0.05). Using multiple regression analysis, we confirmed this influence, and these results were supported by Shariff et al Among AWD mothers, the OC are employed significantly more often in higher rank or leading positions ( P = 0.039), and the data of Friedman et al confirmed these observations.…”
Section: Discussionsupporting
confidence: 82%
“…In our opinion, an essential factor to estimate if the mother's lifestyle was healthy or not was maternal nicotine, alcohol, and illicit drug use before and during pregnancy. Numerous studies described a relationship between the occurrence of GS and maternal smoking . In our cohort, GS mothers drank, smoked, and used illicit drugs more often than OC and CG mothers, yet we found a significance only for alcohol ( P = 0.05).…”
Section: Discussioncontrasting
confidence: 57%
“…Fewer cases of gastroschisis were diagnosed in the first trimester compared to exomphalos cases. Gastroschisis is an opening of the abdominal wall on the right side of the umbilical cord . When the fetus is visualized in the mid‐sagittal view used for the crown–rump length measurement, the defect may be overlooked, unlike an abdominal wall defect within the umbilical cord insertion like exomphalos.…”
Section: Discussionmentioning
confidence: 99%
“…The observed trend in gastroschisis could be related to a variety of factors. In addition to young age, gastroschisis has been associated with smoking and being unmarried (Friedman et al, ), as well as with lower educational attainment (Husain et al, ; Friedman et al, ). Husain et al () also found increased parity to be related to decreased gastroschisis in general, which logically coincides with young mothers having fewer pregnancies and greater prevalence of gastroschisis.…”
Section: Discussionmentioning
confidence: 99%